PEMASARAN JERUK SIAM KINTAMANI - Ni Luh Nilayani; I Ketut Arnawa; Ni Putu Sukanteri (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This study is to analyze marketing costs, marketing margin, farmer income, marketing efficiency and inhibiting factors in marketing institutions. Sampling using the theory of Slovin as many as 67 farmers. The number of samples was taken by taking proportional random sampling, with the analysis method of marketing margin, farmer share, and marketing efficiency. The results of the research on Siamese oranges in Bayunggede Village showed that channel I totaled 20 people, channel II amounted to 27 people, channel III amounted to 20 farmer respondents. Based on the results of research on the marketing of siam oranges in Bayunggede Village, Kintamani District, Bangli Regency, the following conclusions are obtained: The largest margin in this study is in channel III: amounting to Rp. 7,000. The biggest Farmer Shere is on channel I at 100%. The most efficient marketing efficiency is at marketing channel I at 0.00%, and channel II at 37.50%. The biggest marketing obstacle to farmers is the price of oranges which has decreased by 65%, the biggest obstacle to collectors is the high transportation cost of 66.66%, the biggest obstacle to retailers is the number of damaged oranges as much as 62 ,5%. The biggest obstacle to consumers is the price of oranges which is expensive as much as 80%.